PENYULUHAN PERGAULAN BEBAS BAGI REMAJA DESA MALAKASARI BALEENDAH KABUPATEN BANDUNG - Alderajat Mudayanah, Allyka; Toharudin, Andi; Yulvani Pertiwi, Citra; Putri, Mayarani; Zulbetti, Rita (ABISATYA DINAMIKA ISWARA PUBLISHING, 2023)
Promiscuity is a form of deviant behavior or crossing the boundaries of applicable norms. Promiscuity in Malakasari Village, especially teenagers in RW 06, needs to be prevented by choosing good friends/environment, and being aware of their own worth. Based on the results of the discussion, there was one resident with experience in taking an approach to straightening out other residents who had fallen into promiscuity. The educational activities carried out by KKN 67 aim to create healthy and characterful families. The method used is a qualitative method with observation techniques, documents and descriptive research. To avoid promiscuity, socialization can be carried out among teenagers regarding the negative impacts of promiscuity. The socialization carried out can be done by educating teenagers or it can also be done by taking a personal approach to the teenagers. This personal approach has a good influence in reducing the prevalence of promiscuity which is currently on the rise.